(untitled) (Revista científica Olimpia, 2019)
The current work pretends to make a theoretical and practical description about the controversial topic of the laterality and its treatment in early school ages, and it also provides up to date terms and criteria related with this theme, as well as the performance of motor skills in the dynamics of Physical Education. This research also offers a ludic proposal that favours the development and strengthening of laterality in the age brackets mentioned before.